The pohuwato resort policy efforts in responding the threating of motor vehicles in the district region - Muhammad Rizal Lampatta (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
Efforts are being made to combat criminal acts of theft in the Pohuwato Regional Police jurisdiction, namely through Pre-emptive efforts, preventive measures and repressive efforts. Operations carried out to combat motor vehicle theft, namely: K2YD Patrol (enhanced police activities), competitive Patrols, and Ranmor Patrol. (2) The Constraints Faced by the Police in Addressing Motorized Vehicles In the Pohuwato Regional Police's Legal Area are Internal Constraints consisting of incomplete Facilities and Infrastructures, Interrupted Information Networks, inadequate members of the police in terms of demand, and support for voting. And External Constraints which consist of a lack of evidence and elections, communities that support the Police, and supporting facilities at the crime scene are inadequate.